'One Can Always Say No.' Enriching the Bioethical Debate on Antisocial Behaviour, Neurobiology and Prevention: Views of Juvenile Delinquents. (29th July 2012) - Horstkötter, Dorothee; Berghmans, Ron; Feron, Frans; De Wert, Guido
ABSTRACT Genomic and neuro‐scientific research into the causes and course of antisocial behaviour triggers bioethical debate. Often, these new developments are met with reservation, and possible drawbacks and negative side‐effects are pointed out. This article reflects on these scientific developments and the bioethical debate by means of an exploration of the perspectives of one important stakeholder group: juveniles convicted of a serious crime who stay in a juvenile justice institution. The views of juveniles are particularly interesting, as possible applications of current and future scientific findings are considered to be most effective if applied early in life. Based on their statements we come to the following provisional conclusions. Concerns about labelling and stigmatization are recognized and widely shared. Possible effects on one's identity are acknowledged too. Yet, a possible biological underpinning of one's antisocial behaviour is not considered to result in the development of a criminal identity. Nonetheless, psychopharmacological interventions are experienced as endangering one's current self. Concerns regarding the refusal of responsibility and the blaming of one's genes or brain can be put into perspective. Instead, participants emphasize the motive of own choice as underlying their criminal behaviour. Moreover, bioethical debate should pay attention to the role of parents of children at risk and the parent‐child relationship in families at‐risk. We argue that the short‐term and long‐term interests of children at risk, as well as their interests and those of society at large, may conflict. In order to deal appropriately with newly arising dilemmas, a normative framework needs to be developed.